Self-efficacy of university teachers - Muhammad, Haneen Younis; Musa, Wathiq Omar (Journal of Tikrit University for Humanities, 2024)
The current research aims to identify the level of self-efficacy of university teachers. It also shows the statistically significant differences in self-efficacy according to the gender variable (male, female) and specialization (scientific, human). To achieve the objectives of the research, the researcher prepared a scale (self-efficacy), consisting of (41) items, and each item had alternatives. The researcher applied the tool to a randomly selected research sample consisting of (300) male and female teachers. They have a high level of self-efficacy, and there are no statistically significant differences according to the variable of gender and specialization.